2015
DOI: 10.1161/atvbaha.115.306014
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Recombinant ADAMTS13 as an Effective Therapy for Acquired Thrombotic Thrombocytopenic Purpura

Abstract: Objective-The metalloprotease ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) regulates the size of von Willebrand factor multimers. A deficiency in ADAMTS13 activity is associated with the life-threatening disease thrombotic thrombocytopenic purpura (TTP). The vast majority of patients have acquired TTP, where circulating anti-ADAMTS13 autoantibodies are causative for the decreased ADAMTS13 activity. Current treatment consists of plasma exchange, but improved thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 28 publications
2
56
0
2
Order By: Relevance
“…It is effective to treat congenital TTP symptoms in mice (312) and acquired TTP symptoms in rats, where rADAMTS13 was able to overcome circulating inhibitors and reconstitute ADAMTS13 activity (313). A Phase I clinical study is currently going on to assess rADAMTS13 in the treatment and prophylaxis of congenital TTP (NCT02216084).…”
Section: Autoantibody-induced Ttp: Anti-adamts13 Antibodiesmentioning
confidence: 99%
“…It is effective to treat congenital TTP symptoms in mice (312) and acquired TTP symptoms in rats, where rADAMTS13 was able to overcome circulating inhibitors and reconstitute ADAMTS13 activity (313). A Phase I clinical study is currently going on to assess rADAMTS13 in the treatment and prophylaxis of congenital TTP (NCT02216084).…”
Section: Autoantibody-induced Ttp: Anti-adamts13 Antibodiesmentioning
confidence: 99%
“…Fibrinogen concentrates and PCCs may provide superior therapy compared to plasma in bleeding patients without genetic deficits due to the possibility of rapid restoration of hemostasis and are under active investigation. Even in TTP, a recombinant ADAMTS13 is in preclinical development, a product that may in future supplement the most evidence-supported indication for plasma transfusion [98]. Given the paucity of evidence of benefit for the medical use of transfusable plasma and the existence of high-level clinical evidence of efficacy for some of the indications for which fractionated products are employed, it is likely that an increasing proportion of plasma will be fractionated rather than transfused.…”
Section: Overview: Assessing the Quality Of Transfusable Plasmamentioning
confidence: 99%
“…showed that rADAMTS13 can neutralize autoantibodies and reconstitute the ADAMTS13 activity in vitro 28. Moreover, pre‐clinical studies using Sprague‐Dawley rats, showed that rADAMTS13 can restore the ADAMTS13 activity by forming ADAMTS‐13 specific immune complexes 29, 30. These data collectively suggest a role for rADAMTS13 in iTTP and may be the rationale for future studies.…”
Section: Recombinant Adamts13 (Radamts13 Bax930)mentioning
confidence: 75%